Ibadah Haji Ditinjau Dari Berbagai Aspek - Budi Kisworo (AL-ISTINBATH : Jurnal Hukum Islam, 2017)
Hajj is a very special worship in Islam. It is the spiritual congress of Muslims worldwide. His position in religion as the fifth pillar of Islam, but in terms of its appeal to the interests of the Muslim community, the pilgrims ranked first. There are no districts or provinces in Indonesia that are waiting list of hajj candidates for only one year. It's all over five years. Hajj comes from the Shari'ah of Prophet Ibrahim. Which was transmitted by the Prophet Muhammad and followed by his people until the end of time. The goal is that mankind wants to imitate the behavior of Prophet Ibrahim, his wife Hajar, and his son Ismail in surrendering in totality to his Lord. The spiritual monument built by Prophet Ibrahim and his family has been practiced and perfected by the Prophet Muhammad. Through the pilgrimage, the spiritual monument built by four central figures, Ibrahim as., Siti Hajar, Ismail as., And Muhammad saw. It would be taken home by every pilgrim as a souvenir to be dedicated to the community in their respective hometown. Not the title of Pak Haji or Bu Hajjah, not white “peci” or white “mukena” as a symbol of hajj mabrur, but "pure heart" as the embodiment of total submission of faith to the Most Own.